2004
DOI: 10.1016/j.ejvs.2003.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and Venous Reconstruction for Free Tissue Transfer in Diabetic Ischemic Foot Ulcers

Abstract: Temporary AV fistula and free flap may provide stable wound coverage and high rate of limb salvage in treatment of diabetic foot ulcers with large tissue loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
0
21
0
3
Order By: Relevance
“…The high level of HRQoL in ambulatory patients is a desirable result after FFR of the lower extremity. Although various other studies have previously reported evidence of patient satisfaction or HRQoL outcomes following FFR, none has so far employed the use of a validated questionnaire in this patient cohort . The evidence has thus far been sporadic and largely anecdotal.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of HRQoL in ambulatory patients is a desirable result after FFR of the lower extremity. Although various other studies have previously reported evidence of patient satisfaction or HRQoL outcomes following FFR, none has so far employed the use of a validated questionnaire in this patient cohort . The evidence has thus far been sporadic and largely anecdotal.…”
Section: Discussionmentioning
confidence: 99%
“…Anterolateral thigh free flap [34][35][36][37] 25 (29.8) 1 (4.0) 0 (0) Radial forearm free flap 23,29,34 19 (22.6) 2 (10.5) 0 (0) Scapular or parascapular free flap 27 8 (9.5) 0 (0) 0 (0) Arteriovenous fistula free flap 38,39 18 ( How can these data be understood? This review analyzes a large number of reports from different surgical groups.…”
Section: Complete Loss (%)mentioning
confidence: 95%
“…Literature review revealed 35 unique papers (Angel et al, 1993;Atiyeh & Musharafieh, 1997;Bruner, Jester, Sauerbier, & Germann, 2004;Cavadas, 2008;Demiri et al, 2009;Depprich, Naujoks, Meyer, Kubler, & Handschel, 2008;Devansh, 1995;Earle, Feng, & Jordan, 1990;Engel, Pelzer, Sauerbier, Germann, & Heitmann, 2007;Ethunandan, Cole, & Flood, 2007;Freedman, & Meland, 1989;Grenga & Yetman, 1987;Hallock, 1988Hallock, , 2012Karanas, Yim, Johannet, Hui, & Lineaweaver, 1998;Kim & Chandrasekhar, 1998;Lin & Butler, 2010;Lin et al, 2004;Lind, McCarthy, Derman, Jacobs, 2012;Moubayed et al, 2015;Mulholland et al, 1993;Oswald et al, 2007;Picard, Tiguemounine, Laure, Chabut, & Goga, 2004;Rand & Gruss, 1994;Rechnic, Edelson, & Fosburg, 1997;Reichenberger et al, 2010;Ritter et al, 1996;Silveira & Patricio, 1993;Sorensen, Muchardt, & Reumert, 1990;Sunar, Aygit, Afsar, Halici, & Duran, 2004;Tan, Cinal, Algan, & Barin, 2015;Threlfall et al, 1982;Vlastou & Earle, 1988;Vlastou, Earle, & Jordan, 1992;Wong, Lin, Fu, & Fang, 2009), which discussed utilizing AV loops in a single-stage approach and twelve papers which discussed utilizing AV loops in a two-stage approach for m...…”
Section: Meta-analysis Literature Reviewmentioning
confidence: 99%